2020
DOI: 10.1007/s40121-020-00330-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Nasopharyngeal Carriage, Serotype Prevalence, and Antibiotic Resistance of Streptococcus pneumoniae in Indonesia

Abstract: In Indonesia, pneumococcal disease represents a considerable public health concern; however, published data on the epidemiology, nasopharyngeal carriage, serotype prevalence, and antibiotic resistance of Streptococcus pneumoniae in this region are limited. Therefore, this article reviews the available data from a variety of sources and also summarizes pneumococcal conjugate vaccine implementation and recommendations in Indonesia and subsequent impact on pneumococcal disease. Regional pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In this study, we found that nasopharyngeal carriage rates of S. pneumoniae were high in primary school children with AOM (73 %), between the ages of 6 and 12, in Indonesia. In general, the incidence of nasopharyngeal carriage among Indonesian children is 55 % (ranging from 31.2–84.5%) [ 20 ]. Another study in aboriginal children vaccinated with pneumococcal vaccines showed that nasopharyngeal carriage rates were high (approximately 77.9 %) in them, with more than half of the children exhibiting otitis media symptoms [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we found that nasopharyngeal carriage rates of S. pneumoniae were high in primary school children with AOM (73 %), between the ages of 6 and 12, in Indonesia. In general, the incidence of nasopharyngeal carriage among Indonesian children is 55 % (ranging from 31.2–84.5%) [ 20 ]. Another study in aboriginal children vaccinated with pneumococcal vaccines showed that nasopharyngeal carriage rates were high (approximately 77.9 %) in them, with more than half of the children exhibiting otitis media symptoms [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are limited data on nasopharyngeal carriage of S. pneumoniae in children with AOM in Indonesia. Since 2017, Indonesia has implemented a regional PCV immunization programme in selected regions [20]. In general, the nasopharyngeal carriage rate of S. pneumoniae is approximately 43-55 % in Indonesian children [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations